Ways of Departing: First German Candidates to the Congregation Catechists of Boroa (Araucania, Chile, 1932-1934); [Formas de Partir: Primeras Aspirantes Alemanas a la Congregación Catequistas de Boroa (Araucanía, Chile, 1932-1934)] - Stipo-Lara, C (Universidad Autonoma de Baja California, 2024)
This work analyzes the discursive strategies of the first German candidates who, between 1932 and 1934, applied to be missionaries of the Catechist Congregation of Boroa in the Araucanía Region. From a gender perspective and through the systematization and cross-referencing of historical archives (calls, letters, autobiographies, questionnaires), we will analyze the encoded interaction between Capuchin priests and candidates. Focusing on the analysis of the candidates letters, we will argue that exceptionalism and the tricks of the weak constituted paradoxical strategies of women whose desires for recognition and autonomy were legitimized through the civilizing vocation of Mapuche pagans. © 2024, Universidad Autonoma de Baja California. All rights reserved.